Organ and Effective Doses from A Multidetector Computed Tomography in Chest Examination - Ratirat Puekpuang; Sivalee Suriyapee; Taweap Sanghangthum; Sornjarod Oonsiri; Puntiwa Insang (Journal of Medical Physics and Biophysics, 2015)
The growth of Multidetector Computed Tomography (MDCT) associated with the large number of images per examination offers many clinical benefits. It is easy to use for radiologist and physician, and these reasons are the cause of increasing exposure for populations rapidly. Organ and effective doses from CT examination are the important quantities to assess radiation risk. The objective of this study is to calculate the organ and effective doses from patient data. The beam data was collected for 30 cases of patient over 20 years old underwent 64 slices GE VCT MDCT scanner in the chest examinations. The computed tomography dose index (CTDI) values were measured in air and in body phantom with SOLIDOSE ionization chamber then the CTDI values and the exposed parameters were entered in ImPACT CT Patient Dosimetry Calculator version 1.0 for calculation of organ and effective doses. The exposure parameters of chest protocol were 120 kVp, 330 mA, 0.6 sec rotation time, and 1.375 pitch. The average scan length was 34.9 cm for the range of 23.1 to 56.5 cm. The high organ doses in the irradiated field occurred in lung, breast, esophagus, heart, stomach, liver, adrenal gland, kidney, pancreas, spleen and small intestine, the maximum dose ranged from 15 to 23.0 mGy. The average effective dose was 8.6 mSv with the range of 5.7 to 13.0 mSv.  The maximum number of scan series of examination was three which made the maximum effective dose of 39.0 mSv. The scan length was one of the variable factors that made the higher organ and effective doses in CT examination. The more series of examination was another factor to increase the organ and effective doses. The estimated radiation risk for cancer and hereditary effect for chest CT examination was about 5 cases for 10,000 populations. This study has shown that the CT doses used in clinical practice are not higher than commonly report but the careful used of radiation must be considered. Estimated organ and effective doses in chest MDCT scanning are a guide line for radiologists and physicians in order to judge the frequency of scan and suitable scan length. Keywords: organ dose, effective dose, Computed Tomography Dose Index, Multidetector Computed Tomography